2014
DOI: 10.3945/ajcn.114.087692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of egg ingestion on trimethylamine-N-oxide production in humans: a randomized, controlled, dose-response study , , ,

Abstract: The consumption of ≥2 eggs results in an increased formation of TMAO. Choline is an essential nutrient that is required for normal human liver and muscle functions and important for normal fetal development. Additional study is needed to both confirm the association between TMAO and atherosclerosis and identify factors, microbiota and genetic, that influence the generation of TMAO before policy and medical recommendations are made that suggest reduced dietary choline intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
157
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(171 citation statements)
references
References 31 publications
9
157
1
4
Order By: Relevance
“…An individual's eating habits over the short term as well as their dietary patterns over time have been shown to alter the concentration of certain species in the gut [15,54]. Furthermore, TMAO is a by-product of the metabolism of carnitine-and choline-containing food products [55,56]. Individuals with certain dietary preferences or restrictions persistent over time may have overly inflated or reduced TMAO levels based on the composition of the gut flora population and the provision of carnitine-and choline-containing food products.…”
Section: Discussionmentioning
confidence: 99%
“…An individual's eating habits over the short term as well as their dietary patterns over time have been shown to alter the concentration of certain species in the gut [15,54]. Furthermore, TMAO is a by-product of the metabolism of carnitine-and choline-containing food products [55,56]. Individuals with certain dietary preferences or restrictions persistent over time may have overly inflated or reduced TMAO levels based on the composition of the gut flora population and the provision of carnitine-and choline-containing food products.…”
Section: Discussionmentioning
confidence: 99%
“…An obligatory role for gut microbiota in both TMA and TMAO formation from ingested PC was confirmed in animal model studies, which included germ-free mice (25), as well as human clinical investigations involving ingestion of egg yolk, isotope-labeled PC, and a cocktail of oral antibiotics (37). Recently, the association between acute egg yolk ingestion and increased plasma and urine TMAO concentrations was independently confirmed in humans (38). Additional studies have shown that L-carnitine, an alternative TMA-containing nutrient found almost exclusively in red meat, similarly serves as a dietary precursor to gut microbial production of TMA and TMAO in both mice and humans (ref.…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 82%
“…Interestingly, only choline (and not betaine or lecithin) was found to produce a detectable rise in urine TMAO excretion in one small human study employing a variety of dietary exposures (30). More recent studies examining ingestion of either hard-boiled egg or egg yolk (37,38,62) or ingestion of trimethyld9-PC (37) have confirmed direct generation of TMAO from PC ingestion in humans. L-carnitine is a TMA nutrient that, in contrast to choline, is not required in our diets, since it is endogenously produced in mammals from dietary lysine, the single most abundant amino acid in plant and animal proteins (30,63,64).…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 87%
See 1 more Smart Citation
“…In a few other studies, TMAO levels in urine and plasma have also been associated 476 with intake of red meat, egg and dairy food (29,32,42,43 Table 7 for details on statistical results. T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 W1 W2 W3 W1 W2 W3 W1 W2 W3 W1 W2 W3 A B…”
mentioning
confidence: 99%